SPATIAL PLANNING POLICY FOR THE NEW STATE CAPITAL IN PENAJAM PASER UTARA REGENCY AND KUTAI KARTANEGARA REGENCY IN EAST KALIMANTAN PROVINCE AND THEIR PROBLEMS - Baren Sipayung (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The plan to move the capital city of Indonesia from Jakarta to East Kalimantan requires consideration of several aspects such as in terms of benefits, facilities, economic impact, risks, and spatial planning. the preparation and management of spatial planning for the new capital city should pay attention to the welfare of the community and resolve problems that may arise in the middle of the process. This study aims to identify problems in the spatial planning process in the New Capital City of Indonesia. The method used is descriptive analysis from various primary and secondary data sources as well as legislation, case approach, and conceptual approach. The results obtained from this study are the need for continuity of spatial planning documents in stages.